Changes in migratory raptor populations in Veracruz, Mexico, - Ruelas Inzunza, Ernesto; Goodrich, Laurie J.; W. Hoffman, Stephen (Instituto de Ecología, A.C., 2010)
Migration counts of raptors have been used as a valid technique to assess population levels. Counts from Veracruz, Mexico, have the potential of generating valuable information for regional- to continental-scale populations of some species and to provide coverage for others that are not monitored elsewhere. This paper evaluates the use of Veracruz migration counts to monitor populations, documents the adjustments made to a currently existing method to analyze migration count data and fit it to the specific properties of our dataset, and presents estimates of population change over a decade. We used long-term, effort-adjusted migration count data to generate annual indexes of abundance. The series of annual indexes is fitted to a polynomial regression to produce an estimate of the annual rate of change. The use of this methodology with Veracruz data shows its usefulness to datasets of many species, as well as limitations to datasets from species with high interannual variation in migration counts, and those recorded rarely. In seven species, the authors found significant population change. Six of them, Swallow-tailed Kite, Mississippi Kite, Cooper’s Hawk, Swainson’s Hawk, Zonetailed Hawk, and Peregrine Falcon show increases at an annual rate between 1.9-15.7% per year-1 in the period 1995-2005. One species, the Northern Harrier, is decreasing at a rate of -8.4% year-1 during the same period. Trends reported here reveal population increases in most cases, and concur with the pattern found in migration counts from surveys such as the Breeding Bird Survey and the Christmas Bird Count.